2011
DOI: 10.1177/193229681100500502
|View full text |Cite
|
Sign up to set email alerts
|

BioRadioTransmitter: A Self-Powered Wireless Glucose-Sensing System

Abstract: We constructed a stand-alone, self-powered, wireless glucose-sensing system called a BioRadioTransmitter by using a radio transmitter in which the radio wave transmission frequency changes with the glucose concentration in the fuel cell. The BioRadioTransmitter is a significant advance toward construction of an implantable continuous glucose monitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…The minimum detectable glucose concentration in this system was ∼0.2 mM and the increase in the frequency saturated at a glucose concentration of ∼20 mM. Later, Sode and co‐workers further developed a BioRadioTransmitter 55 or BioLC‐Oscillator 54 by using a radio‐transmitter circuit instead of IRLED to monitor glucose concentration (the radio wave resonance frequency changes according to glucose concentration) and miniaturized the system by reducing the size of the BFCs (Figure 5B).…”
Section: Substrate Effectmentioning
confidence: 99%
“…The minimum detectable glucose concentration in this system was ∼0.2 mM and the increase in the frequency saturated at a glucose concentration of ∼20 mM. Later, Sode and co‐workers further developed a BioRadioTransmitter 55 or BioLC‐Oscillator 54 by using a radio‐transmitter circuit instead of IRLED to monitor glucose concentration (the radio wave resonance frequency changes according to glucose concentration) and miniaturized the system by reducing the size of the BFCs (Figure 5B).…”
Section: Substrate Effectmentioning
confidence: 99%
“…It should be noted that most papers on biofuel cells do not discuss the problem of their interfacing with electronics, while being concentrated on resolving internal problems of the biofuel cells, such as current efficiency, stability, etc. Two approaches have been applied to resolve the low voltage problem: (i) assembling biofuel cells in series electrically, thus increasing the total output voltage [59,[70][71][72], and (ii) collecting produced electrical energy in capacitors / charge pumps for the burst release in short pulses [73][74][75][76]. The latter approach has already been applied for activating a wireless transmitting electronic device, however using nonimplantable enzyme-based [76,77] or microbial biofuel cells [73].…”
Section: Interfacing Implanted Biofuel Cells With Biomedical Micmentioning
confidence: 99%
“…The second approach based on electronic interface devices such as charge pumps and other forms of DC-DC convertors has already been applied for the activation of a wireless transmitting electronic device; however, using nonimplantable enzyme-based [76,77] or microbial biofuel cells [73]. The application of an interface device to increase the voltage is rather well-known [78], however it should be remembered that the voltage increase is achieved at the expense of the current consumed by the charge pump, thus putting additional demand on the current output of the biofuel cell.…”
Section: Interfacing Implanted Biofuel Cells With Biomedical Micmentioning
confidence: 99%
“…45 The microneedle arrays were fabricated by following the methods reported by Trzebinski et al 46 The authors reported a closed loop system comprising a CGM sensor and an insulin pump interfaced via suitable control software for management of type 1 diabetes mellitus. The functionalization of working electrodes with glucose dehydrogenase was carried out by following the methods reported by Hanishi et al and Yamashita et al 47,48 The Direct electron transfer (DET) allows the operation of the electrochemical sensor at lower potentials to minimize the effect of interference from acetaminophen, ascorbic acid and uric acid. The design of the microprobe array electrodes is such that the arrays are partitioned into working, reference and background compensation electrodes to enable parallel measurements of glucose and the background currents, respectively.…”
Section: Min For 3 H With a Commercial Glucose Meter Used As Controlmentioning
confidence: 99%